Chemical Composition and Petrogenetic Implications of Eudialyte-Group Mineral in the Peralkaline Lovozero Complex, Kola Peninsula, Russia - Lia Kogarko; Troels F. D. Nielsen (Minerals, 2020)
Lovozero complex, the world’s largest layered peralkaline intrusive complex hosts gigantic deposits of Zr-, Hf-, Nb-, LREE-, and HREE-rich Eudialyte Group of Mineral (EGM). The petrographic relations of EGM change with time and advancing crystallization up from Phase II (differentiated complex) to Phase III (eudialyte complex). EGM is anhedral interstitial in all of Phase II which indicates that EGM nucleated late relative to the main rock-forming and liquidus minerals of Phase II. Saturation in remaining bulk melt with components needed for nucleation of EGM was reached after the crystallization about 85 vol. % of the intrusion. Early euhedral and idiomorphic EGM of Phase III crystalized in a large convective volume of melt together with other liquidus minerals and was affected by layering processes and formation of EGM ore. Consequently, a prerequisite for the formation of the ore deposit is saturation of the alkaline bulk magma with EGM. It follows that the potential for EGM ores in Lovozero is restricted to the parts of the complex that hosts cumulus EGM. Phase II with only anhedral and interstitial EGM is not promising for this type of ore. Nor is the neighboring Khibiny complex despite a bulk content of 531 ppm of Zr. Khibiny only has interstitial and anhedral EGM. The evolution of the Lovozero magma is recorded in the compositions EGM up through a stratigraphy of 2400 m in Phase II and III of the complex, and distinct in elements like rare earth elements (REE), Sr, Ba, Th, U, Rb, Mn, Fe. The compositional evolution reflects primarily fractional crystallization processes within the magma chamber itself in combination with convective magma flow and layering by precipitation of minerals with different settling velocities. The suggested mechanism for the formation of the EGM deposits is flotation of very small, suspended EGM crystals in the convective magma and concentration below the roof of the magma chamber. Phase III EGM is enriched in total REE (1.3%) and in HREE (Ce/Yt = 8.8) and constitutes a world ...